Algunas consideraciones acerca del paralelo ético-jurídico en Religión de Kant - Quiroga, Noelia Eva (Pontificia Universidad Católica del Perú. Fondo Editorial, 2021)
En este trabajo me propongo contribuir a comprender el paralelo ético-jurídico trazado en Religión dentro de los límites de la mera razón. Analizaré las semejanzas, las diferencias y la analogía entre el estado de naturaleza, el exeundum y la comunidad éticos, por un lado, y el estado de naturaleza, el exeundum y la comunidad jurídico-políticos, por el otro. Argumentaré que el progreso moral, entendido como superación del mal radical, requiere un complemento entre el dominio ético y el jurídico-político, dado que cada dominio aporta un abordaje y una solución comunitaria diferente dentro de la misma esfera pública.

“Some Reflections on the Ethical-legal Parallel in Kant’s Religion”. The aim of this paper is to contribute to understanding the ethical-legal parallel drawn in Religion within the Boundaries of Mere Reason. I will analyze the similarities, differences and the analogy among the ethical state of nature, the exeundum and the community, on the one side, and the juridical state of nature, the exeundum and the community, on the other. I will argue that moral progress, understood as overcoming radical evil, requires a complement between the ethical and legal-political spheres, given that each area provides a different approach and a different community solution within the same public sphere.
Some Reflections on the Ethical-legal Parallel in Kant’s Religion
Keywords: Kant; Estado de naturaleza; Comunidad; Deber; Progreso; https://purl.org/pe-repo/ocde/ford#6.03.01